The Potency of Mesenchymal Stem Cells as Viral Oncolytic Carriers - Rakhman, Muhammad Farid (Clinical and Research Journal in Internal Medicine, 2024)
Oncolytic viruses (OVs) represent a category of viruses that selectively replicate within tumor cells, destroying cancer cells through a dual mechanism involving viral oncolysis and the stimulation of the host's anti-tumor immune response. This selectivity ensures the virus targets and eliminates cancer cells while sparing healthy cells. Oncolytic virus immunotherapy refers to treatments utilizing either native or genetically modified OVs designed to replicate within tumor cells selectively. Mesenchymal Stem Cells (MSCs) have demonstrated potential in facilitating the safe transportation and targeted release of oncolytic viruses at the tumor site due to their inherent tumor-specific homing capability. Utilizing MSCs as carriers for oncolytic viruses can enhance the delivery of these therapeutic agents to the tumor site, eliminating the need for direct tumor injection and reducing the associated side effects.